Loss of GAS5 tumour suppressor lncRNA: an independent molecular cancer biomarker for short-term relapse and progression in bladder cancer patients - Avgeris, M.; Tsilimantou, A.; Levis, P. K.; Tokas, T.; Sideris, D. C.; Stravodimos, K.; Ardavanis, A.; Scorilas, A. (Br J Cancer, 2018)
BACKGROUND: Bladder cancer (BlCa) heterogeneity and the lack of personalised prognosis lead to patients' highly variable treatment outcomes. Here, we have analysed the utility of the GAS5 tumour-suppressor lncRNA in improving BlCa prognosis. METHODS: GAS5 was quantified in a screening cohort of 176 patients. Hedegaard et al. (2016) (n = 476) and TCGA provisional (n = 413) were used as validation cohorts. Survival analysis was performed using recurrence and progression for NMIBC, or death for MIBC. Internal validation was performed by bootstrap analysis, and decision curve analysis was used to evaluate the clinical benefit on disease prognosis. RESULTS: GAS5 levels were significantly downregulated in BlCa and associated with invasive high-grade tumours, and high EORTC-risk NMIBC patients. GAS5 loss was strongly and independently correlated with higher risk for NMIBC early relapse (HR = 2.680, p = 0.011) and progression (HR = 6.362, p = 0.035). Hedegaard et al. and TCGA validation cohorts' analysis clearly confirmed the association of GAS5 loss with NMIBC worse prognosis. Finally, multivariate models incorporating GAS5 with disease established markers resulted in higher clinical benefit for NMIBC prognosis. CONCLUSIONS: GAS5 loss is associated with adverse outcome of NMIBC and results in improved positive prediction of NMIBC patients at higher risk for short-term relapse and progression, supporting personalised prognosis and treatment decisions.
Keywords: Aged; Biomarkers, Tumor/*analysis; Disease Progression; Female; Humans; Male; Neoplasm Recurrence, Local/*genetics; Prognosis; RNA, Long Noncoding/*analysis; Urinary Bladder Neoplasms/*genetics/mortality